School performance and child labor: Evidence from West Bank schools - Sameh Hallaq; Ayman Khalifah (Levy Economics Institute of Bard College, 2022)
The current study aims to investigate the impact of academic achievement on child labor. The study utilizes survey data collected from Palestinian children in West Bank schools who are in the primary grades (5th-9th). The results show that increasing a child's academic achievement is significantly associated with decreasing the probability that a child works for money in the following period. Our findings varied among children according to their gender, age, and parental academic background. Our analyses are subject to different specifications, including two-stage least squares (2SLS) to account for potential endogeneity. The results provide robust evidence about the linkage between school performance and child labor in the West Bank. Further, the study proposes an assessment of the child's mental health problems by the Strengths and Difficulties Questionnaire (SDQ) as a potential mechanism through which the child's achievement at school affects child labor.
Keywords: D15; I21; J13; I12; 330; Academic Achievement; Child Labor; West Bank